2009
DOI: 10.1111/j.1471-4159.2009.06061.x
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 9 prevents MPP+‐induced death of dopaminergic neurons and is involved in melatonin neuroprotection in vivo and in vitro

Abstract: Abbreviations used: BDNF, brain-derived neurotrophic growth factor; BSA, bovine serum albumin; DA, dopamine; FGF, fibroblast growth factor; GDNF, glial cell line-derived neurotrophic factor; MAP2, microtubule associated protein 2; MTT, 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide; PBS, phosphate-buffered saline; PD, Parkinson's disease; TH, tyrosine hydroxylase; TH-ir, TH-immunoreactive. AbstractOxidative stress and down-regulated trophic factors are involved in the pathogenesis of nigrostriata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
1
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 58 publications
(118 reference statements)
0
39
1
3
Order By: Relevance
“…Because MPP + is the major active and toxic metabolite of MPTP and uptake by dopamine transporter, but cannot cross the blood-brain barrier (Dauer and Przedborski, 2003), we directly infused MPP + into the rat striatum to avoid the effect of exercise on MPTP metabolism and to specifically destroy the nigral dopamine neurons (Chen et al, 2002;Huang et al, 2009;Hung et al, 2008). One microliter of 50 mM MPP + (Sigma-Aldrich, St. Louis, MO, USA) or PBS was infused into the right striatum through a 30-gauge stainless steel cannula connected to a 10 μl microsyringe (Hamilton Co., Reno, NV) in an infusion rate of 0.1 μl/min using a syringe pump and kept still for 5 min before being slowly withdrawn to minimize possible physical damage to the brain tissue.…”
Section: Intracerebral Drug Injectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because MPP + is the major active and toxic metabolite of MPTP and uptake by dopamine transporter, but cannot cross the blood-brain barrier (Dauer and Przedborski, 2003), we directly infused MPP + into the rat striatum to avoid the effect of exercise on MPTP metabolism and to specifically destroy the nigral dopamine neurons (Chen et al, 2002;Huang et al, 2009;Hung et al, 2008). One microliter of 50 mM MPP + (Sigma-Aldrich, St. Louis, MO, USA) or PBS was infused into the right striatum through a 30-gauge stainless steel cannula connected to a 10 μl microsyringe (Hamilton Co., Reno, NV) in an infusion rate of 0.1 μl/min using a syringe pump and kept still for 5 min before being slowly withdrawn to minimize possible physical damage to the brain tissue.…”
Section: Intracerebral Drug Injectionmentioning
confidence: 99%
“…Our previous studies have shown that the antioxidant action of melatonin attenuates the elevation of ROS and the reduction of glutathione thus preventing dopaminergic neuron death due to 1-methyl-4-phenylpyridine (MPP + , the major bioactive and toxic metabolite of MPTP) toxicity in vivo and in vitro (Chen et al, 2002;Chuang and Chen, 2004;Huang et al, 2009). A significantly lower level of glutathione was also found in brains of patients with PD (Elokda et al, 2010;Sian et al, 1994), while dopaminergic glutathione depletion resulted in age-related nigrostriatal dopaminergic neurodegeneration (Chinta et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In neurodegenerative diseases, FGF9 signaling has been reported to affect cellular or pathological features in Alzheimer's disease (AD) and Parkinson's disease (PD) [5,[15][16][17]. For example, FGF9 is surrounding senile plaques in AD brain [15,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, FGF9 is surrounding senile plaques in AD brain [15,18]. In PD models, FGF9 provide neuronprotective effects from apoptosis through γ-glutamylcysteine synthetase and heme oxygenase 1 expression [5,16]. These suggest the involvement of FGF9 signaling in neuropathology and disease progression of AD and PD.…”
Section: Introductionmentioning
confidence: 99%
“…Functionally, the literature suggests that FGF9 may promote cell survival. For example, FGF9 acts as a survival factor for nigrostriatal and mesencephalic dopamine neurons (24), and FGF9 treatment can increase the survival and soma size of cultured basal forebrain cholinergic neurons (25). FGF9 also weakly promoted proliferation and survival of cultured adult subventricular neural progenitor cells, inhibiting astrocyte differentiation (26).…”
mentioning
confidence: 99%